The influences of parenting stress, children behavioral problems and children quality of life on depression symptoms among parents of children with autism: preliminary findings - Ainul Izzah Abdul Manan,; Noh Amit,; Zaini Said,; Mahadir Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Taking care of children with Autism Spectrum Disorder (ASD) could be a demanding task for parents. Consequently, parents of children with ASD may experience parenting stress and depression symptoms. This study examined parenting stress and depression symptoms among parents of children and adolescents with ASD. This study also examined the role of child characteristics (e.g., age, child quality of life and problem behavior) on parenting stress and depression symptoms and the effect of parenting stress on parental depression. A total of 78 parents were examined using a questionnaire survey. The result indicated that parents caring a younger age group of children with ASD have higher levels of depression symptoms compared to parents caring for older group of children with ASD. The result also revealed a significant difference in level of depression symptoms between parents with higher levels of parenting stress and parents with lower parenting stress. Only the children age significantly predicts depression symptoms in parents of children with ASD. This indicates that children age is potential to affect mental health among parents of children with ASD.